Hija de mal padre. Identidad nacional y Dictadura en el Paraguay - Ana Inés Couchonnal Cancio (Centre de Recherches sur les Mondes Américains, 2020)
Nationalism in Paraguay is an ideological element consolidated during the dictatorship of Alfredo Stroessner. The article address the anchoring of the nationalist discourse that survived the dictatorial regime of Alfredo Stroessner to roam as common sense in the murky waters of what has been called transition to democracy. We briefly consider the grounds of the nationalist discourse built in the postwar period and its particular implementation and development during the Stroessner government. Then we introduce an analytical scheme of the ideological effectiveness of this discourse that works as a transversal axis to the political structure inherited from the dictatorship. We argue that the nationalist discourse forged during the dictatorship reproduced a family scheme assigning places to the different members of the society and that this resulted into a kind of genealogy that culminated in the dictator but managed to transcend it. Finally, we hope to introduce a wedge to think about other possible identitarian modes within a society that crosses a tense present between both options.